Design and Development of a Single-Phase Induction Motor Module as an Educational Tool - Muhammad Iham Fatqurrochman; Anggara Trisna Nugraha; Rama Arya Sobhita (Maritime in Community Service and Empowerment, 2025)
In the field of education, particularly in marine electrical engineering, knowledge of single-phase capacitor motors is essential. To equip students with a solid understanding of the principles and operation of single-phase capacitor AC motors, appropriate infrastructure and learning tools, such as trainer kits, are required. A trainer kit functions as a basic educational tool that enhances comprehension of single-phase capacitor induction motors, which is crucial for students studying specialized courses in electrical motors. This tool enables various practical experiments, such as measuring the insulation resistance of motor windings, reversing the motor's rotation, testing the starting process of capacitor motors, and analyzing the power factor of capacitor motors. Additionally, a single-phase induction motor with a capacitor start can be used as a split-phase motor. The starting current in a split-phase motor is higher compared to a capacitor-start induction motor because the capacitor increases the starting power, resulting in a smaller current compared to the split-phase motor.